PENGENALAN DASAR SENSOR FACE RECOGNITION DAN COMPUTER VISION - Surtikanti; Akbar Juliandi; Ade Rahman; Akbar Fauzi Mutaqin; Angelus Defananda; Aldi Pratama; Hibatullah Zuhdii; Muhammad Iqbal (Abdi Jurnal Publikasi, 2025)
The advancement of digital technology has significantly impacted the education system, including within Madrasah Tsanawiyah (MTs) institutions. Face recognition and computer vision are two major fields in artificial intelligence that are increasingly applied across industries and education. This Community Service Program (PKM) aims to provide fundamental knowledge about how facial recognition and computer vision technologies work to students at MTS An-Nur Wangunjaya. The methods used include surveys, literature studies, and Focus Group Discussions (FGD) to tailor the material to students’ needs. The results of the program indicate a growing interest among students in technology and highlight the importance of early digital literacy development.